Political Performances of Control During COVID-19: Controlling and Contesting Democracy in Germany - Volk, Sabine (Frontiers in Political Science, 2021)
Drawing from interpretive, namely discursive-performative approaches to both institutional and grassroots (populist) politics, this article explores political performances and counter-performances of control in Germany during the so-called first wave of the COVID-19 pandemic. Methodologically, the article constructs a comparative analytical framework including three cases from both within and outside of Germany’s federal institutional structure: At institutional level, the cases comprise Angela Merkel, Germany’s long-term federal chancellor, and Michael Kretschmer, the regional governor of the state of Saxony; at grassroots level, the selected case is the populist protest movement PEGIDA. Based on original empirical data generated using the toolkit of qualitative-interpretive methodology, notably online ethnography, the comparative analysis focuses on a few key (counter-)performances of control, among them a TV address (Merkel), a visit to an ‘anti-lockdown’ demonstration (Kretschmer), and virtual protest events (PEGIDA). Emphasizing the performed, dynamic, and contested character of political control in Germany in spring 2020, the empirical analysis yields the following results: First, it sheds light on the different political styles of performing and contesting institutional control, including the habitus, modes and (emotional) tones of communication of the performers, as well as the scripts, stages, intended audiences as (imagined) constituencies, and modalities of transmission of their performances. Second, the discourse-theoretical perspective of the analysis reveals that political performances of control were closely linked to articulations of democracy as an empty signifier, and to claims to safeguard democratic principles as such. Third, the article demonstrates the value of interpretive approaches to politics to generate more nuanced understandings of the relationships between pandemic, democracy, and populism in a situation of an ultimate lack of control.